Delayed type hypersensitivity induced by intradermal inoculation of a Neospora caninum tachyzoite antigen in previously exposed cattle - Fiorani, Franco; Armendano, Joaquín Ignacio; Hecker, Yanina Paola; Araoz, Virgina; Canton, German Jose; Leunda, Maria Rosa; Pereyra, Susana Beatriz; Corva, Pablo Marcelo; Odeon, Anselmo Carlos; Moore, Prando Dadin (Elsevier, 2019)
The aim of this study was to evaluate delayed type hypersensitivity (DTH) induced by the intradermal inoculation of a Neospora caninum tachyzoite soluble lysate in cattle previously exposed with the protozoa. Four experimental groups were selected according to the prior exposure to N. caninum antigen. All cows were intradermally injected with a N. caninum tachyzoite soluble lysate and skinfold thickness growth at the inoculation sites was measured at 0, 24, 48, 72 and 96 h post inoculation (hpi). Additionally, specific antibodies and IFN-γ production were assessed. Cows experimentally infected with live N. caninum tachyzoites and cows naturally exposed to N. caninum developed skin reactions compatible with DTH between 24 and 96 hpi (p < 0.05). Moreover, cows inoculated with an experimental N. caninum vaccine and cows without evidence of exposure to N. caninum did not show a significant increase in skin thickness (p > 0.05). Furthermore, serological status of the animals was not modified due to the intradermal inoculation. The highest IFN-γ production was observed at 15 days after intradermal inoculation (p < 0.05). Therefore, these results suggest that cattle previously exposed to N. caninum develop a reaction compatible with DTH which could be useful as in vivo cell mediated immunity parameter for assessed bovine neosporosis.